Performance of chilli (Capsicum annuum L.) genotypes for growth and yield parameters in eastern dry zone of Karnataka - S D Nehru, K Jyothi, H M Vijaya, A P M Gowda, (Journal of Spices and Aromatic Crops, 2014)
The present experiment was undertaken to evaluate 24 chilli genotypes for different growth and yield parameters. The genotype ‘Chikballapur Local’ was found to have maximum plant height (118.6 cm) and plant spread (0.481 m2) while, genotype ‘Sankeshwar’ recorded higher number of primary branches plant-1 (7.47) and maximum fruit length (14.61 cm). Genotype ‘Byadgi Dabbi’ registered maximum fruit diameter (1.60 cm), pericarp weight (0.80 g), stalk weight (0.14 g) and number of seeds fruit-1 (98.42). The higher number of fruits plant-1 (186.30) and dry fruit yield (97.33 g plant-1) were recorded in the genotype ‘Sankeshwar’ followed by genotype LCA-206.